The impact of offshore and gas exploitation on the marine environment and its regulations under selected national regimes - Fombang, Humphrey (Centre for Law and Society, 2026)
Despite the numerous advantages accrued from the exploitation of oil and gas worldwide, the repercussion of its activities on the marine environment has put the entire world under panic about the future of our beloved planet. Political leaders from both developed and developing countries through Conventions, Conferences, national policies and legislation, have been seeking various ways to regulate the exploitation of oil and gas on the continental shelf and Exclusive Economic Zone in order to protect the marine environment that is at the brink of losing its socio-economic values. With the present trend of events threatening the planet such as climate change and the call for sustainable development, the regulation of oil and gas exploitation on the marine environment remains a dilemma. It is now crystal clear that the principle of 'Common but Differentiated Responsibilities' as advocated by both the Rio and Johannesburg world summits on sustainable development, with regard to the regulations of oil and gas exploitation, which have already been put in place, must be strengthened.